Coping with Disasters While Living in Poverty: A Systematic Review. Issue 5 (4th July 2018) - Krishna, Revathi N.; Majeed, Saadia; Ronan, Kevin; Alisic, Eva
ABSTRACT: This review synthesizes the literature on how Asia-Pacific children and families living in poverty cope with disasters. A systematic search yielded 26 studies from six low- and middle-income countries (LMIC) in the region. Findings emphasized the role of socioeconomic factors, sociocultural factors, and indigenous knowledge. Coping strategies related to finances were most prominently described in the studies, in contrast to health and psychosocial strategies. Substantial gender issues were identified. The review highlights gaps regarding child involvement in research and coping strategies used by children living in poverty.